LINGUODIAGNOSTIC IN PRACTICE OF DOCTOR-STOMATOLOGY - Ilenko, N.M.; Nikolishina, E.V.; Marchenko, A.V. (World of Medicine and Biology, 2012)
Pathology of different systems of human body reflects in changes on a dorsal surface of the tongue even before the main signs of the nervous, cardio-vascular, digestive and endocrine disorders.